Increase in drug resistance among Shigella dysenteriae, Sh flexneri, and Sh boydii. Issue 6291 (29th August 1981) - Gross, R J; Rowe, B; Cheasty, T; Thomas, L V
Abstract : Two thousand three hundred and seventy strains of Shigella dysenteriae, Sh flexneri, and Sh boydii isolated in England and Wales from 1974 to 1978 were tested for resistance to 12 antimicrobial drugs. Eighty per cent of strains were resistant to one or more drugs, with sulphonamide resistance occurring most frequently. Resistance to streptomycin, tetracycline, ampicillin, and chloramphenicol increased during the period, as did the incidence of multiple resistance. Most infections due to Sh dysenteriae, Sh flexneri, and Sh boydii are acquired abroad, and the increasing incidence of drug resistance among these organisms contrasts with the decreasing incidence of resistance among the indigenous Sh sonnei. These findings may indicate the need for better control of antibiotic use, particularly in developing countries.